Hypertension in a resource‐limited setting: Is it associated with end organ damage in older adults in rural Tanzania?. Issue 2 (15th February 2018) - Putnam, Harry W. I.; Jones, Rebecca; Rogathi, Jane; Gray, William K.; Swai, Bernadetha; Dewhurst, Matthew; Dewhurst, Felicity; Walker, Richard W.
Abstract : Few data from sub‐Saharan Africa exist on the effects of hypertension on the organs of the human body. We aimed to establish the prevalence of hypertensive end organ damage (EOD) in an elderly cohort of Tanzanians. The population aged 70 years and over of 2 villages in northern Tanzania (n = 246), had blood pressure (BP) data available from 2010 and 2013, and underwent in‐depth follow‐up for markers of hypertensive EOD in 2016. Assessment included ankle‐brachial pressure index, lying‐standing BP, electrocardiogram, and mid‐stream urine dip. Sustained hypertension (those with hypertension at all 3 assessments) was found in 129 (52.4% subjects). Of the entire cohort, 13.9% had left ventricular hypertrophy and 26.4% had peripheral arterial disease, both of which were associated with sustained hypertension, although orthostatic hypotension, stroke, proteinuria, and arterial stiffening were not. Further investigation, particularly in younger age groups, is merited if hypertension‐associated morbidity is to be controlled.